The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.24315/tred.1141882
|View full text |Cite
|
Sign up to set email alerts
|

Türki̇ye’de Eği̇ti̇m Alaninda Bi̇li̇m Merkezi̇ Konusunda Gerçekleşti̇ri̇len Araştirmalarin İçeri̇k Anali̇zi̇

Abstract: Bu çalışmanın amacı, Türkiye’de eğitim alanında bilim merkezleri konusunda yapılan araştırmaları çeşitli özellikler açısından betimsel olarak incelemektir. Nitel araştırma desenlerinden biri olan doküman analiz kullanılarak; eğitim alanında bilim merkezlerini konu alan, Türkiye’de gerçekleştirilen, 2022 yılı ocak ayına kadar ulusal düzeyde yayımlanan ve tam metni elektronik olarak erişime açık olan makale ve lisansüstü tez türündeki 68 adet yayın derinlemesine bir şekilde betimlenmiştir. 68 adet yayından elde … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
0
0
Order By: Relevance
“…Apart from this, while there are a few studies on social studies (Öner & Öztürk, 2019; Özmen & Öner, 2022), it has been observed that there are no domestic studies in pre-school education. Akın and Demirdöğen (2023) concluded in their research where they examined academic studies on science centers in the field of education that there were no studies on pre-schooll education. Therefore, it can be said that the research is important because it is one of the first studies conducted in this field.…”
Section: Extended Abstractmentioning
confidence: 99%
“…Apart from this, while there are a few studies on social studies (Öner & Öztürk, 2019; Özmen & Öner, 2022), it has been observed that there are no domestic studies in pre-school education. Akın and Demirdöğen (2023) concluded in their research where they examined academic studies on science centers in the field of education that there were no studies on pre-schooll education. Therefore, it can be said that the research is important because it is one of the first studies conducted in this field.…”
Section: Extended Abstractmentioning
confidence: 99%